Analisis Framing pada Teks Editorial Tentang Buntut Panjang Olokan 'Goblok' Gus Miftah ke Penjual Es Teh : Studi Kasus pada Media Online Detik.com - Mutiara Pangaribuan; Dian Saphira (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to analyze the framing in the editorial text of detik.com regarding the article titled "Buntut Panjang Olokan ‘Goblok’ Gus Miftah ke Penjual Es Teh" using Robert N. Entman's framing model. The research focuses on how the editorial presents the issue, the selection of certain aspects of the story, and the implications of these choices on public perception. By employing Entman's framework, the study identifies the key elements of framing, including problem definition, causal interpretation, moral evaluation, and treatment recommendations. The findings reveal how the editorial shapes the narrative around the incident, influencing readers' understanding and attitudes towards the involved parties.